Hybrid : the history and science of plant breeding - Kingsbury, Noel (University of Chicago Press, 2009)
"Starting his story at the birth of agriculture, Kingsbury traces the history of human attempts to make plants more reliable, productive, and nutritious--a story that owes as much to accident and error as to innovation and experiment. Drawing on historical and scientific accounts, as well as a rich trove of anecdotes, Kingsbury shows how scientists, amateur breeders, and countless anonymous farmers and gardeners slowly caused the evolutionary pressures of nature to be supplanted by those of human needs--and thus led us from sparse wild grasses to succulent corn cobs, and from mealy, white wild carrots to the juicy vegetables we enjoy today. At the same time, Kingsbury reminds us that contemporary controversies over the Green Revolution and genetically modified crops are not new; plant breeding has always had a political dimension"--Book jacket.